Peran Perencanaa Pembelajaran Terhadap Kualitas Pengajaran - Tasha aina; Windi putri arisqa; Ayu fitria siregar; Safran hasibuan (CV. ITTC INDONESIA, 2023)
Learning planning plays a role in optimizing the use of learning time. Teachers can organize logical learning sequences, prioritize important learning topics, and avoid wasting time. This allows teachers to cover all aspects of learning well. Learning planning also has an impact on learning evaluation. Teachers can plan evaluations that are in line with learning objectives, use valid evaluation instruments, and collect accurate data about student achievement. With a good evaluation, teachers can see to what extent learning objectives are achieved, identify students' weaknesses and strengths, and make necessary improvements in teaching. Overall, learning planning has an important role in improving the quality of teaching. With good planning, teachers can direct teaching more effectively, provide learning experiences that are relevant and appropriate to student needs, and ensure that learning objectives are achieved well.